PEMBATALAN PERKAWINAN AKIBAT HUBUNGAN SESUSUAN DITINJAU BERDASARKAN KOMPILASI HUKUM ISLAM - Bobi Riyanto (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTMarriage is one of the important things in human life, especially in social life. Basically, marriage has a long-term goal, as is the desire of humans themselves in order to foster a harmonious, peaceful and happy life in an atmosphere of love from the two types of creatures created by Allah SWT, realizing a marriage, of course there are requirements and prohibitions. - prohibitions that must be known by both parties who will enter into a marriage for the sake of the validity of the marriage. That is, if the marriage is carried out without paying attention to what are the conditions and prohibitions of marriage, then the marriage is considered invalid and can be canceled. Law Number 1 of 1974 concerning Marriage and Article 70 of the Compilation of Islamic Law, namely the prohibition of marriage between siblings.The type of research used is normative legal research or library law research because it is in the form of secondary data such as legislation and literature books. From the results of the study, it was concluded that in Islamic law marriage annulment can occur due to two things, namely there are things that cancel the marriage contract that is carried out, and there are new things that are experienced after the marriage contract occurs and the temporary marriage relationship takes place, Breastfeeding marriage is prohibited by law religion and also by state law because breastfeeding marriages are marriages that occur between a man and a woman where both breastfeed on the same mother so that they are called breast-feeding siblings. As for the legitimacy of the legitimacy of a marriage in which both parties are still bound by a breastfeeding relationship in terms of the Compilation of Islamic Law, Breastfeeding marriages that have been or are in progress are invalid or invalid bylaw and the law of the marriage is unlawful, so that the marriage can be annulled. or in other words, the breastfeeding marriage can be annulled because the marriage has taken place, it is confirmed in the Compilation of Islamic Law Article 39 number 3 letter c of the Compilation of Islamic Law. In accordance with the conclusions above, it is hoped that people who are considered to know or understand the law if they can help disseminate information about breast- feeding marriages starting from the scope of the family and the community around where they live, also the government is more stringent in conducting inspections of data before marriage, namely regarding the status of marriage. and the validity of the data of each party who will carry out the marriage so that unwanted things do not happen, such as requests to cancel the marriage. Key words: Breastfeeding Marriage, Cancellation of Breastfeeding Marriage